Establishment of a Molecular Serotyping Scheme and a Multiplexed Luminex-Based Array for Enterobacter aerogenes - Guo, Xi; Wang, Min; Wang, Lu; Wang, Yao; Chen, Tingting; Wu, Pan; Chen, Min; Liu, Bin; Feng, Lu (Frontiers in Microbiology, 2018)
Serotyping based on surface polysaccharide antigens is important for the clinical detection and epidemiological surveillance of pathogens. Polysaccharide gene clusters (PSgcs) are typically responsible for the diversity of bacterial surface polysaccharides. Through whole-genome sequencing and analysis, eight putative PSgc types were identified in 23 Enterobacter aerogenes strains from several geographic areas, allowing us to present the first molecular serotyping system for E. aerogenes. A conventional antigenic scheme was also established and correlated well with the molecular serotyping system that was based on PSgc genetic variation, indicating that PSgc-based molecular typing and immunological serology provide equally valid results. Further, a multiplex Luminex-based array was developed, and a double-blind test was conducted with 97 clinical specimens from Shanghai, China, to validate our array. The results of these analyses indicated that strains containing PSgc4 and PSgc7 comprised the predominant groups. We then examined 86 publicly available E. aerogenes strain genomes and identified an additional seven novel PSgc types, with PSgc10 being the most abundant type. In total, our study identified 15 PSgc types in E. aerogenes, providing the basis for a molecular serotyping scheme. From these results, differing epidemic patterns were identified between strains that were predominant in different regions. Our study highlights the feasibility and reliability of a serotyping system based on PSgc diversity, and for the first time, presents a molecular serotyping system, as well as an antigenic scheme for E. aerogenes, providing the basis for molecular diagnostics and epidemiological surveillance of this important emerging pathogen.